Service Partner Superannuation Process Efficiency and Employees Satisfaction of Payroll Solution Company: Basis for Action Plan - Amor, Kimberly V.; Bucal, Remedios J.; Pendon III, Fernando T. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examines the relationship between the efficiency of service partner superannuation processes and employee satisfaction within a payroll solutions organization. As a key component of employee benefits, superannuation requires accuracy, timeliness, and regulatory compliance. The research focuses on how efficient processes, specifically in lodgement, payment, and ad hoc requests, affect employee satisfaction, particularly in terms of reliability, responsiveness, assurance, and empathy. A quantitative approach was used, with data collected through a structured survey among operations department employees. Responses were measured using a Likert scale. Statistical tools such as descriptive analysis, Pearson correlation, and regression were employed to evaluate the relationship between process efficiency and employee satisfaction. Findings indicate that the superannuation processes show moderate to high efficiency, especially in lodgement, payments, and ad hoc services. Employees reported a generally positive experience, with high trust in process reliability and responsiveness. However, opportunities for improvement remain, particularly in enhancing transparency, real-time support, and personalized service. These gaps highlight the need for more proactive and individualized engagement to elevate the employee experience from adequate to excellent. Improving responsiveness and feedback mechanisms can strengthen morale, boost productivity, and promote a more resilient workforce. Finally, the study confirms a statistically significant link between superannuation process efficiency and employee satisfaction. Streamlined operations not only reduce delays and errors but also reflect the organization's dedication to quality and reliability—factors critical to employee and customer perceptions. Continuous process improvement is essential to maintaining competitiveness in an evolving market.